Precise micro-fabrication of structures to enhance photon collection from diamond color centers - Hadden, J; Marseglia, L; Stanley-Clarke, A; Kennard, J; Harrison, J; Ho, Y; Patton, B; Rarity, J; O'Brien, J (2011)
Diamond color centers show promise in quantum photonics applications. However practical implementation is limited by low photon collection efficiency. We report precise fabrication of structures which substantially increase collection efficiency from color centers. © 2010 Optical Society of America.